Regional variations and trends in ambient noise: Examples from australian waters - McCauley, R.; Cato, D.; Duncan, Alec (2016)
Studies of ambient noise south of Australia show higher levels at low frequencies in the deep water off the continental shelf compared with locations on the shelf. The difference arises because of differences in transmission loss. Marine animals would experience significantly different noise levels and directionality in the two regions and while crossing the boundary, provide positional information. Opportunities for long-range, low-frequency communication by animals would be significantly limited by the higher background noise in the open ocean. Measures of long-term sea noise trends highlight the influence of biological sources and the importance of local sound transmission regimens.